The Effects of Corporate Governance on Audit Quality: An Empirical Study of Non-Financial Companies Listed on the Idx (2020-2022) - Salira, Aprilia; Prasetyo, Andrian Budi (Formosa Journal of Sustainable Research, 2024)
This study aims to examine the effects of corporate governance on audit quality. Board size, independent commissioners, institutional ownership and financial literacy of the audit committee are independent variables in this study. The dependent variable in this study is audit quality. Control variables are also involved in this study, which include firm size and firm age. The logistic regression analysis method was used in this study. All data used was obtained from the annual reports of non-financial companies listed on the Indonesia Stock Exchange for 2020-2022. A total of 936 samples were selected using a purposive sampling method. The study results show that board size and financial literacy of the audit committee have a significant positive effect on audit quality. Independent commissioners and institutional ownership also have a positive effect but not significant on audit quality. These findings may indicate that increasing the board size and the presence of audit committee members who have accounting knowledge can improve audit quality in the company